Conductive Coatings of 2D MXene-in Water for Electronics Applications: A Recent Study - Radhika, T. (Current Approaches in Science and Technology Research Vol. 10, 2021)
In situ HF etching method was used to prepare the Ti3C2Tx based MXene. Simple procedures such as dip coating, drop casting, and vacuum filtration were used to coat this MXene-in-water formulation on various substrates. The conductivity of the coatings measured with four probe method shows high conductivity and varies (1-50 Scm-1) depending on the method and coating of the thickness. This conductive coatings with MXene-in-water formulation achieved through simple procedures holds promise for electronics, energy storage, and healthcare applications.